2019
DOI: 10.1016/j.jbo.2019.100228
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA UCA1 promotes osteosarcoma metastasis through CREB1-mediated epithelial-mesenchymal transition and activating PI3K/AKT/mTOR pathway

Abstract: Highlights UCA1 is upregulated in both osteosarcoma tissues and cell lines. UCA1 promotes osteosarcoma metastasis both in vitro and in vivo. UCA1 increased CREB1 expression by functioning as a ceRNA of CREB1 against miR-582. The pro-metastasis role of UCA1 is achieved by promoting EMT. UCA1 enhances EMT through CREB1-mediated the PI3K/Akt/mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…A similar study documented that SOX2OT can attenuate the binding of miR‐194‐5p to SOX3 3′UTR by competitively binding to miR‐194‐5p, thus accelerating the development of glioma . Another study reported that UCA1 can attenuate the inhibitory effect of miR‐582 on CREB1 by competitively binding to miR‐582 to promote the occurrence and development of osteosarcoma . HMMR‐AS1 is able to attenuate its inhibitory effect on SIRT6 by competitively binding to miR‐138, accelerating the development and progression of lung adenocarcinoma …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A similar study documented that SOX2OT can attenuate the binding of miR‐194‐5p to SOX3 3′UTR by competitively binding to miR‐194‐5p, thus accelerating the development of glioma . Another study reported that UCA1 can attenuate the inhibitory effect of miR‐582 on CREB1 by competitively binding to miR‐582 to promote the occurrence and development of osteosarcoma . HMMR‐AS1 is able to attenuate its inhibitory effect on SIRT6 by competitively binding to miR‐138, accelerating the development and progression of lung adenocarcinoma …”
Section: Discussionmentioning
confidence: 87%
“…48 Another study reported that UCA1 can attenuate the inhibitory effect of miR-582 on CREB1 by competitively binding to miR-582 to promote the occurrence and development of osteosarcoma. 49 HMMR-AS1 is able to attenuate its inhibitory effect on SIRT6 by competitively binding to miR-138, accelerating the development and progression of lung adenocarcinoma. 50 We also observed the upregulation of the mRNA and protein expression levels of LASP1 by TFAP4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…19 It is urgent to investigate new and effective molecular targets for the treatment of RB. In this study, 16 ovarian cancer 22 and lung cancer. 23 Furthermore, Sun et al 24 have reported that lncRNA-UCA1 is highly expressed in laryngeal squamous cell carcinoma.…”
Section: Rbmentioning
confidence: 97%
“…30 A study of Li et al 17 has indicated that lncRNA-UCA1 significantly promotes cell proliferation and suppresses apoptosis by activating PI3K-Akt-mTOR signaling pathway in gastric cancer. Ma et al 16 have suggested that lncRNA-UCA1 could promote osteosarcoma metastasis through the activation of PI3K/AKT signaling pathway. In the present study, silencing lncRNA-UCA1 significantly decreased the phosphorylation of PI3K and Akt, as well as the expression of S6k in HXO-RB44 cells, while lncRNA-…”
Section: Rbmentioning
confidence: 99%
“…PI3K/Akt pathway has been considered to exert a crucial impact in tumor. 11−13 In OS, Ma H et al 14 have revealed that LncRNA UCA1 promotes OS metastasis through EMT by activating PI3K/AKT/mTOR pathway. MDA19 has been reported to inhibit OS cell metastasis by PI3K/Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%